PENERAPAN STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING MELALUI LESSON STUDY UNTUK MENINGKATKAN KETERAMPILAN MEMECAHKAN MASALAH MAHASISWA - Mustofa, Zainul; Khoiriyah, Anna Jarrotul; Sulistiyawati, Indah; Harmawati, Diah; Al Muhdhar, Mimien Heni Irawati (Jurnal Pendidikan Biologi, 2016)
This research aims at improving students' problem solving skills. The type of research used is Classroom Action Research by implementing Lesson Study-based Problem Based Learning strategy as an effort to improve students’ problem solving skills. This study was conducted for 1 cycle consisting of two meetings. The results of this research show that LS-based PBL strategy can improve students' problem solving skills, from 30% during observation to 93%. The data of students' average problem solving skill scores reached 80.07. The achievement of this score has met the minimum standard score of State University of Malang, which is 55.00. Based on these results, learning by using LS-based PBL strategy can improve students' problem solving skills.